Dr Ambedkar and democracy : an anthology - Ambedkar, B. R.; Jaffrelot, Christophe; Kumar, Narender (New Delhi, OUP, 2018)
This anthology brings together Dr. Bhimrao Ambedkar's works on the theme of Democracy. The editors of this volume have assembled Ambedkar's original writings including his memorandums, speeches, lectures, and talks from 1919-1956 to understand his contribution to Indian political thought and history. An introductory chapter binds the anthology together by helping put in context Ambedkar's arguments and perceptions within contemporary debates on Democracy. It captures Ambedkar's political trajectory and addresses how his idea of Democracy is deeply embedded in both the colonial and the post-colonial context. The editors argue that Democracy is not merely a procedural and substantive idea, but relational as well and in Ambedkar it is deeply caught with ideas ofstate, power, nationalism, constitutionalism, equality, and liberty, thus emphasizing its societal and as well as political dimensions. The anthology therefore helps readers think through contemporary political debates in the country within the context of a critical overview of Ambedkar's thoughts on Democracy.
"Indian Institute of Dalit Studies."
Includes bibliographical references and index.
Keywords: Democracy -- India